Epidemiological correlates with communicable viral co-infections of hepatitis B and hepatitis C and non-communicable diabetes among HIV ART naïve rural patients of Kanchipuram district: a prospective cohort study - Kasthuri, A.; Mohana Krishnan, K.; Amsavathani, S. K. (International Journal Of Community Medicine And Public Health, 2018)
Background: The objectives of the study were to study the epidemiological correlates of ART Naïve HIV cases; to study the incidence of co–infections among them; to find the incidence of onset of diabetes among them. Concomitant infection of hepatitis B virus, hepatitis C virus viruses leads to higher frequency of carrier state and severe manifestations of the disease in HIV patients. There is general agreement that the traditional risk factors for DM (increasing age, minority race, obesity) are still responsible for most of the increased risk in the HIV infected population. Methods: This study was designed as a prospective cohort study and was done at the Meenakshi Medical College & Research institute, an academic and Tertiary medical centre in Kanchipuram, Tamil Nadu, South India. The study duration was from June 2004 to June 2010. SPSS 13 was used in the calculation of chi-square and percentages. Results: Among 207 participants, mean age is 36.04 and the SD is 10.895. There is significant difference between the incidence of viral co-infections like hepatitis B and hepatitis C (p<0.001). There is significant difference between the incidence of onset of diabetes (p<0.001). The HbsAg and HCV co infection was comparatively lower than the urban population. Among the 50 HIV reactive, non diabetic patients without risk factors, only one found to be Diabetic and another found to be Pre diabetic after 6 months follow-up. Conclusions: The cost of treatment escalates, when PLHA is co-infected either with viral infections or diabetes, and also their quality of life becomes poor. So, monitoring of CD4 and CD8 should be done as a routine and screening and early treatment should be made mandatory.